Practical approaches to method validation and essential instrument performance verification - Chan, Chung Chow.; Lam, Herman.; Zhang, Xue-Ming. (Wiley, 2010)
"The objective of this book is provide information in same practical, hands-on manner as the first book "Analytical Method Validation and Instrument Performance Verification", on important, but more advance topics. It will focus on additional and supplemental methods, instruments, and electronic systems that are used in pharmaceutical, biopharmaceutical, and clinical testings. These tests will generate reliable data that is in compliance with current Good Manufacturing Practices (cGMP) and will follow Good Analytical Practices"--Provided by publisher.